Novel SHAL base derived cobalt containing organic semiconducting metallogel thin film for self-powered high-performance photodetector application - Pandey, Vinay Kumar; Kim, Young Hoon; Choi, Hwayong; Dubey, Mrigendra; Hasan, Sayad Hadi; Heo, Junseok; Pandey, Rajiv Kumar (Optical Materials, 2023)
The development of new materials with facile synthesis and better semiconducting and photonic properties is crucial for the fabrication of durable thin film-based semiconductor devices. In this study, an organic semiconducting and photo-conducting metallogel has been obtained by deprotonation of the ligand SHAL using LiOH followed by treatment with Co(II) acetate in dimethylformamide (DMF) under ambient conditions. Various characterization techniques are used to analyze the mechanical, morphological, and optical properties. This analyses reveal the formation of a organic semiconducting Co(II)-metallogel with a nanofibrous architecture. Furthermore, a comprehensive analysis of this material in thin film form demonstrates its n-type organic semiconducting nature with a good rectification ratio in the Schottky diode configuration, among the best-known values of all these materials. The Co(II)-metallogel is analyzed based on its semiconducting properties as a self-powered (in absence of external bias voltage) photodetectors (PDs) in an ITO/Co(II)-metalogel/Au configuration, for the first time. The measured photocurrent demonstrates responsivity, R(λ), of 2.77 x 103, 0.27 x 103, and 0.025 × 103 mA/W, external quantum efficiency (EQE) of 73.4 x 104, 63.1 x 103, and 25 x 103, and detectivity (D) of 5.28 x 1012, 5.2 x 1011, 4.7 x 109 Jones, with on/off ratio of 16 080, 1580, and 150 at 0 V under the illumination of 470-nm (blue), 530-nm (green), and 630-nm (red) light sources, respectively. The high performance of the PDs is attributed to the UV–vis spectrum of the thin film, morphology, and metal-semiconductor energy band schematic outcomes. Overall, this study presents considerable potential for novel applications of Co(II)metallogels in technologically challenging electronic and optoelectronic devices.
Keywords: High responsivity; Organic semiconducting metallogel; Organics; Photovoltaic property; Responsivity; Schottky junctions; Self-powered; Self-powered photodetector; Thin-film devices; Thin-films; High responsivity; Organic semiconducting metallogel; Photovoltaic property; Schottky junction; Self-powered photodetector; Thin film devices